TanDEM-X DEM Calibration Concept and Height References - Hueso-Gonzalez, Jaime; Bachmann, Markus; Fiedler, Hauke; Krieger, Gerhard; Zink, Manfred (European Conference on Synthetic Aperture Radar (EUSAR), 2008)
TanDEM-X is the first bistatic space borne SAR mission and it is formed by adding a second, almost identical spacecraft to TerraSAR-X and flying them in a closely controlled formation. The primary goal of the mission is the derivation of a high-precision global Digital Elevation Model (DEM) according to HRTI level 3 quality. To achieve this accuracy, height references have to be applied in the calibration of the DEM, together with a least squares adjustment of adjacent interferograms. Content of this paper is the description of the general DEM calibration concept and the summary of the different analysis and research activities to validate it, with special stress on the height references selection.
DLR Import::2019-04-03